2013
DOI: 10.1007/s00586-013-2873-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the dural sac of patients with lumbar canal stenosis evaluated by multidetector-row computed tomography after myelography

Abstract: Purpose Some reported studies have evaluated the dural sac in patients with lumbar spinal stenosis (LSS) by computed tomography (CT) after conventional myelography or magnetic resonance imaging (MRI). But they have been only able to evaluate static factors. No reports have described detailed dynamic changes in the dural sac during flexion and extension observed by multidetector-row computed tomography (MDCT). The aim of this study was to elucidate or demonstrate, in detail, the influence of dynamic factors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(22 reference statements)
1
13
1
Order By: Relevance
“…Thirdly, and to add complexity, spinal canal stenosis should be perceived as a dynamic phenomenon. A lot of spinal canal stenosis subjects report position-dependent symptoms due to postural changes in the dimensions of the spinal canal[12,37].…”
Section: Spinal Canal Stenosismentioning
confidence: 99%
“…Thirdly, and to add complexity, spinal canal stenosis should be perceived as a dynamic phenomenon. A lot of spinal canal stenosis subjects report position-dependent symptoms due to postural changes in the dimensions of the spinal canal[12,37].…”
Section: Spinal Canal Stenosismentioning
confidence: 99%
“…Specifically, forward flexion and relaxed supine position provide larger spinal canal volume, thus relieving neurological symptom. While extension position can decrease its volume and reduce dural sac cross-sectional area [ 21 24 ]. Preoperative images of CT or MRI are often acquired in relaxed supine position, so it may underestimate severity of lumbar canal stenosis to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have described dynamic changes in the lumbar dural sac [2021222324]. Kanbara et al [21] reported that bulging of the ligamentum flavum had 50%–85% contribution to spinal canal narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…Kanbara et al [21] reported that bulging of the ligamentum flavum had 50%–85% contribution to spinal canal narrowing. Thus, bulging of intervertebral discs is expected to contribute to spinal canal narrowing under loading conditions by approximately 15%–50%.…”
Section: Discussionmentioning
confidence: 99%